(untitled) (Stavební obzor - Civil Engineering Journal, 2024)
This paper takes a prestressed π-shaped beam cable-stayed bridge in China as an engineering case, and conducts relevant research on the overall and local parameter sensitivity of the structure and the stress characteristics under cable damage. The main factors causing cable damage in the prestressed π-shaped beam cable-stayed bridge are analyzed, and the selection of elastic modulus as a damage variable is determined. Based on the finite element model analysis of the actual bridge, different inclined cables are selected for damage simulation, and the dynamic variation characteristics of the main beam, cables, and other structures under one-sided, symmetrical, and asymmetrical cable damage are analyzed. This provides a reference for the dynamic performance analysis of prestressed π-shaped beam cable-stayed bridges under similar cable damage conditions in the future.